2018
DOI: 10.1136/bmjopen-2017-021288
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with current VTE prophylaxis guidelines and risk factors linked to complications of VTE prophylaxis in medical inpatients: a prospective cohort study in a Spanish internal medicine department

Abstract: ObjectivesTo evaluate the degree of compliance with the current guidelines regarding venous thromboembolism (VTE) prophylaxis in medical patients during admission and to identify risk factors linked to complications of VTE prophylaxis.DesignProspective cohort study.SettingThe Internal Medicine Department of the University Hospital of Santiago de Compostela (tertiary referral hospital).ParticipantsA total of 396 hospitalised, elderly patients who did not undergo surgery and had no active or previous oral antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The enoxaparin prescription pattern identified in the present study was inappropriate, similar to the studies by Fahimi et al and Nekoonam B et al As shown in the study by Fahimi et al [27], the improper dosing, administration, and prescription of enoxaparin occur frequently, and health care providers require training programs and the implementation of evidence-based protocols to control prescription patterns. Regarding complications, a study by Novo-Veleiro et al [28] reported wound haematoma (7.3%) and major bleeding (0.5%) as the main complications, while wound haematoma occurred in 16.6% of patients and no major bleeding was noted during and after hospitalization in our study.…”
Section: Discussionsupporting
confidence: 50%
“…The enoxaparin prescription pattern identified in the present study was inappropriate, similar to the studies by Fahimi et al and Nekoonam B et al As shown in the study by Fahimi et al [27], the improper dosing, administration, and prescription of enoxaparin occur frequently, and health care providers require training programs and the implementation of evidence-based protocols to control prescription patterns. Regarding complications, a study by Novo-Veleiro et al [28] reported wound haematoma (7.3%) and major bleeding (0.5%) as the main complications, while wound haematoma occurred in 16.6% of patients and no major bleeding was noted during and after hospitalization in our study.…”
Section: Discussionsupporting
confidence: 50%
“…In the thrombosis risk assessment of cancer patients, various relevant laboratory indicators should be fully integrated to make the prevention and treatment of cancer-related VTE more targeted and individualized. 37 Several studies 38,39 have pointed out prophylactic anticoagulation therapy with low-molecular-weight heparin in patients with cancers can improve the patient's prognosis, reduce the risk of VTE and clinical mortality. All anticoagulation therapy should be closely observed for signs of bleeding during use.…”
Section: Discussionmentioning
confidence: 99%
“…The harms of bleeding-including substantial case fatality rates-may be under-appreciated. Many authors have argued that declining rates of VTE in hospitalized patients should be cause for re-appraisal and de-escalation of previous protocols for the use of VTE prophylaxis [7,8]. As the baseline rate of VTE changes, either through time or differing circumstance, we must balance the threats of both underuse and overuse of pharmacologic VTE prophylaxis.…”
Section: Bleeding Complications Limit the Net Benefits Of Thrombopropmentioning
confidence: 99%
“…This approach is easy to implement in patient care, and pharmacologic VTE prophylaxis for medical and surgical inpatients is frequently included in admission order sets for these patients. However, recent evidence suggests the risk of bleeding with anticoagulant thromboprophylaxis negated its benefit in some groups of patients [7][8][9]. Subsequent trials are examining whether it is possible to improve upon this approach by developing a risk prediction tool to identify individuals with high VTE risk who would benefit the most from thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%